One-step, rapid fluorescence sensing of fungal viability based on a bioprobe with aggregation-induced emission characteristics. (10th February 2020) - Ge, Xiaoxue; Gao, Meng; Situ, Bo; Feng, Weiwei; He, Bairong; He, Xiaojing; Li, Shiwu; Ou, Zihao; Zhong, Yiqi; Lin, Yahui; Ye, Xinyi; Hu, Xiumei; et al.
Abstract : A smart AIEgen has been developed to rapidly (5 minutes) and precisely differentiate fungal viability in a wash-free manner. Abstract : Fungi play key roles in various fields, including fermentation-based industries, medicine, and public health. The rapid and precise evaluation of fungal viability is critical for fungi-related fields. However, the methods currently applied have a series of limitations, such as time-consuming, laborious, and cumbersome. In this study, we designed and synthesized a water-dispersible fluorescent probe DPASI with typical aggregation-induced emission (AIE) characteristics for selectively lighting up dead Candida cells within 5 minutes. The rapid staining of the dead Candida cells could be ascribed to the efficient binding of DPASI with mitochondria, which was revealed by high-resolution fluorescence images taken by a structured illumination microscope (SIM) and colocalization images taken by a confocal laser scanning microscope (CLSM). Compared with traditional probes for the identification of dead Candida cells, the DPASI probe does not require tedious centrifugation and washing steps and has significant advantages in time-and-labor-saving. It thus provides a facile and promising tool for the rapid evaluation of antifungal susceptibility and screening of new antifungal drugs, which would greatly contribute to the fungal research.